Compression Test and Finite Element Analysis of Foamed Concrete Cube - Goh, W.I.; Mohamad, N.; Abdullah, R.; Samad, A.A.A. (Journal of Engineering and Technology (JET), 2014)
Foamed concrete is one of the most economical and industrialized construction materials in modern building construction market either for conventional construction technique or precast construction technique. However, the damage behavior of foamed concrete had not been explored deeply by researchers especially for its continuum damage mechanics and plasticity. This paper presents the results of compressive tests and finite element analysis of foamed concrete cubes. The focus of this paper is on the compressive behavior of foamed concrete. Three dimensional- nonlinear finite element model was developed and analyzed by the aquasi static technique using the ABAQUS explicit module. The input parameters of the model were obtained from experimental results. Concrete damaged plasticity was chosen as damaged criteria. Results show that the proposed finite element model is able to predict the damage behavior of the foamed concrete cube accurately. Thus, finite element method can be used as an economical tool for studying the structural behavior of foamed concrete in compression.